E-learning Difficulties Facing Arabic Language Teachers in the Directorate of Education in Damascus - Drwish, Drwish Hasan; Engin, Ali Osman (Journal of Educational and Psychological Sciences, 2021)
This study aims to reveal the obstacles in using the E-learning from the viewpoint of Arabic language teachers in the Directorate of Education in Damascus. It also aims to identify the impact of academic specialization and attainment of the international Computer Driving License on these difficulties. In order to achieve this goal, the researcher followed the descriptive analytical method, where a questionnaire of 24 items developed after revealing its reliability and validity. Where this sample was composed of 390 teachers who worked at the Directorate of Education in Damascus. Relevant statistical tests conducted, where the survey of items discussed established the difficulties faced by Arabic teachers while using E learning. The majority of difficulties faced by these teachers related to administrative and financial problems, followed by difficulties of using E- learning itself, whereas the last third part in difficulties is related to schools and learners.